Implementasi Model Pembelajaran STEAM Terhadap Minat Belajar Siswa - Rofiah Rofiah (https://journal.metanusantara.com/pedagogia, 2024)
21st century education demands innovative learning models that can increase students' interest in learning. The STEAM (Science, Technology, Engineering, Arts, Mathematics) learning model comes as an interdisciplinary approach that integrates various fields of science to create a more contextualised and applicable learning experience. This research aims to find out the implementation of the STEAM learning model in increasing students' interest in learning at the primary and secondary school levels. This research uses a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation studies. The research informants consisted of teachers and students in schools that have implemented STEAM-based learning. The results showed that STEAM implementation increased students' interest in learning by creating a more active, collaborative and problem-solving-based learning environment. Students showed increased intrinsic motivation, engagement in scientific exploration, and critical and creative thinking skills. In addition, this study also found that the main challenges in STEAM implementation are teacher readiness, limited facilities, and the need for a more comprehensive evaluation system.